Computational analysis to “A formula that generates prime numbers”: Análisis computacional a “Una fórmula que genera números primos” - Miramontes de León, Gerardo (2022)
The computational code of “A formula that generates prime numbers” is analyzed, which was published in Vol. 22, No. 1 of Revista digital Matemática, Educación e Internet and which was presented as a function a(n) given by:Here it is shown that, for each value of n, that formula reduces to a loop of the simplest primality test, that is, by trial division. It is shown, step by step, that a(n) includes operations that can be avoided, such as extracting the fractional part, and two rounding operations. It is concluded that this “formula that generates prime numbers” is actually a non-optimized proof of primality by trial division, since, for example, it does not avoid testing even values of n.